PEMBERDAYAAN MASYARAKAT MELALUI PEMBUATAN PERMEN SAPI POTONG DI KENAGARIAN SUNGAI KUNYIT KABUPATEN SOLOK SELATAN - Ferry Lismanto Syaiful; Khasrad Khasrad; Fauzia Agustin; Rusmana Rusmana; Mahdiatul Hafizoh (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
Cow candy is a feed supplement that contains a source of protein, energy and minerals needed by livestock. This cow candy is shaped on and rich in nutrients which is used to increase beef cattle productivity. Cow candy is very useful in growing microbes in the rumen, adding energy, growing lust, and fattening. This activity aims to: 1. increase beef cattle population / productivity through cow candy making in Kenagarian Sungai Kunyit Solok Selatan, 2. improve breeders 'understanding of making beef candy as feed for Nagari River Kunyit beef cattle, 3. improve breeders' skills in making candy cattle, and 4. the application of technology from the campus to the Sungai Kunyit nagari community. This activity was carried out in June 2019 which involved Unand students, breeders and the community in Nagari Sungai Kunyit. The method of this activity is in the form of counseling, demonstration, guidance, coaching and evaluation. From the implementation of the activity, the results of the activities are as follows: 1. The response of farmers / community is very high following the activities of counseling and demonstration of cow candy, 2. Improving the understanding of breeders / community in making cow candy, 3. Increasing the income / welfare of the community in the business of cow candy. This activity was categorized as successful after evaluating the activity and benefiting breeders / community of Sungai Kunyit, South Solok.